(untitled) (Journal of Economic Research & Business Administration, 2017)
Benchmarking in the tourism sector - an ongoing process of study and evaluation of tourism products and experience their most serious competitors or those travel agencies that are recognized by business leaders (not necessarily direct competitors, and not necessarily just the tourism industry of the company). This search for the best experience of commercial activity, which leads to an advantage in the tourism business. It involves the process of assessing the internal state of things in the travel agency and the external evaluation, which is based on certain objective facts that are continuously collected. The article describes the international experience and the importance of using awards in the tourism industry to improve the company’s competitiveness. Also investigated the company leaders in the tourist market of Kazakhstan in different areas, which experience can use the other participants of this market.